Mary and the witch's flower [videorecording (DVD)] - Yonebayashi, Hiromasa, 1973-; Stewart, Mary, 1916-2014 (Universal Pictures Home Entertainment, 2018)
A strange flower grants a young girl magical powers, which leads to the adventure of a lifetime.